Hamlet: the Advent of Modernity - FÉREZ MORA, PEDRO ANTONIO (Cartaphilus, 2012)
Hamlet is such an obscure, impenetrable and nuanced writing that it has been prey to a runaway interpretative voracity on the part of the critics. This boundless fertility has fostered imagination excessively, most of the times, to the detriment of a unitary study of the play. In fact, criticism in general has made of Hamlet a bunch of unconnected fragments. T. S. Eliot soon perceived the dangers of carrying out this kind of literary analysis.